MENINGKATKAN POLA ASUH POSITIF MELALUI PENYULUHAN PARENTING BAGI ORANG TUA DI KAMPUNG CIHANJUANG DESA PANGEURENAN - Infa Azizah, Fela; Nawwaroh, Zahra (Al-Mu'awanah: Jurnal Pengabdian kepada Masyarakat, 2025)
Positive parenting supports children’s socioemotional development and autonomy. However, many parents in rural communities still rely on inherited practices and have limited access to evidence-based information and psychosocial support. This community service–based study aimed to strengthen parents’ understanding and practical skills related to positive parenting and maternal mental health through a participatory parenting counseling program in Kampung Cihanjuang, Desa Pangeurenan. The activities included interactive lectures, group discussions (FGD), question–answer sessions, and motivational support involving the KKN 169 team, village officials, and local health cadres. Data were collected through participatory observation, documentation, and discussion notes, complemented by short feedback forms. The program was attended by around 50 mothers and showed high engagement. The findings indicate improved awareness of empathetic communication, consistent rules, and positive reinforcement, as well as a better understanding of the risks of authoritarian and permissive parenting. The activity also initiated peer support among mothers and encouraged community involvement to sustain family empowerment efforts. Overall, participatory parenting counseling is a feasible approach to promote positive parenting practices in rural settings.